DARI POTENSI MENJADI PROFIT: Optimalisasi Peran BUMDES Singa Barong sebagai Pilar Pemberdayaan Ekonomi Desa dan Strategi Dakwah - Fida Try Rahma; Khusnul Khotimah (PT. Cadas Insan Madani, 2026)
BUMDes Singa Barong Kebarongan is a government program to help improve the economy of the Kebarongan Village community and realize community welfare so that they can live decently. The purpose of this study is to determine how the implementation of empowerment da'wah in order to improve the economy of the Kebarongan Village community through BUMDes Singa Barong. This study is a qualitative descriptive study, with the object of BUMDes Singa Barong located in Kebarongan Village. The data were obtained from observation, interviews, and documentation. The results of the study indicate that BUMDes Singa Barong contributes to the economic development of Kebarongan Village and community empowerment in line with the principles of empowerment in Islam, namely Ukhuwwah, Ta'awun, and Equality of Degree.